Bank's Cost Efficiency and Loan Loss Provisions Behaviours: An Empirical Analysis Based on US Commercial Bank - Huang, Ying-Xuan (2019)
This research paper mainly focuses on the cost efficiency and loan loss provisions (LLPs) behaviours of 96 commercial banks in the US from 2009 to 2018. The first stage is based on the stochastic frontier method (SFA) model to estimate cost efficiency, which finds that US commercial banks have a high level of cost efficiency. And the second stage uses the system Generalised-Method-of-Moment (GMM) estimation to analyse the LLPs behaviours of commercial banks, including income smoothing, business cycle, capital management, and efficiency. More importantly, the results of cost efficiency that obtained in the first stage is a variable to test efficiency hypothesis in the second stage. The result of GMM indicates that the behaviours of income smoothing through LLPs was not common in US commercial banks during the period. At the same time, LLPs generally show a pro-cyclical trend and the behaviours of capital management are also found. However, there is no evidence of a significant relationship between LLPs and efficiency